2012
DOI: 10.21273/hortsci.47.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variations in Buddleia Induced by Gamma Ray Irradiation

Abstract: Buddleia species is commonly used as a perennial for landscaping as a result of its heavy flowers and long bloom period. However, this species has a few concerns such as lack of flower color, excessive growth, and an invasive nature. Attempts to improve Buddleia using conventional breeding methods have resulted in limited success. In this study, mutagenesis by gamma ray irradiation was used to induce genetic variations. In vitro shoot tips of two Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The low r 2 value for all variables reflects the variability of our data. Similar to our study, variability in morphological traits in response to radiation dose has also been observed in gamma-irradiated shoot tips of Buddleia cultivars (Dai and Magnusson, 2012). Given the random nature of mutation treatments to DNA, this is not unexpected.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The low r 2 value for all variables reflects the variability of our data. Similar to our study, variability in morphological traits in response to radiation dose has also been observed in gamma-irradiated shoot tips of Buddleia cultivars (Dai and Magnusson, 2012). Given the random nature of mutation treatments to DNA, this is not unexpected.…”
Section: Resultssupporting
confidence: 90%
“…Radiation can affect plant height by reducing the number of nodes and the length of internodes (Gottschalk and Wolff, 1983). Radiation has been used as a tool to induce mutations for the development of commercial varieties in many crop species, particularly the forages as well as in ornamental crops such as Chyrsanthemum (Dao et al, 2006), Dendranthemum grandiflorum (Datta et al, 2001), Nelumbo nucifera (Arunyanart and Soontronyatara, 2002), Rosa hybrida (Arnold et al, 1998;Gupta and Shukla, 1971;van Harten, 1998), and Buddleia (Dai and Magnusson, 2012).…”
mentioning
confidence: 99%
“…Some researchers hypothesised that the plasma membrane and cytosolic enzyme systems suffer damage that can lead to inhibition of plant growth and development under high dose of radiation (Fu et al, 2000;Anandhi et al, 2013). We observed that irradiation also caused a series of morphological variations in leaves and flower shapes (Dai and Magnusson, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…A similar finding was reported by Srivastava and Mishra (2005), who spotted smaller flowers in Hibiscus rosa-sinensis plants exposed to gamma irradiation. Other reports indicated that varied flower sizes were observed across gamma-irradiated plants, such as in chrysanthemum (Lamseejan et al, 2000), Calisthepus chinensis (Anwar et al, 2020) and Buddleia (Dai and Magnusson, 2012). Additionally, fewer flowers ranging from three to four were produced in contrast to the control plants with five to eight flowers (Table 1).…”
Section: Morphological Characterization Of 15-gy Irradiated P Aphrodi...mentioning
confidence: 88%